(untitled) (International Journal of Gender, Science and Technology, 2018)
It is no secret that the ‘glass ceiling’ preventing women advancing to leadership positions exists in academia as well. Spain is no exception. Gender relations are usually investigated independently of other power relations like class and ethnicity. In our sample (80 men and women in different academic institutions across Spain) we found that not only women but also men from working class backgrounds have difficulties making successful academic careers. Therefore, we use an intersectional approach to investigate the relationship between gender and class. Comparing two life-histories, we explore what strategies individuals employ to overcome the barriers with which they are confronted. We present the stories of a woman with a middle class but non-academic background and of a man with a working-class background. Their strategies can be understood as the result of specific individual trajectories under specific societal conditions, but they also illustrate the barriers and possibilities men and women with non-standard backgrounds encounter in academia. Analysing successful strategies as well as their limitations, we aim to provide perspectives that might contribute to changing the culture of hegemonic masculinities in academia.&